Computational Analysis of Non-Kekule Benzenoid Molecules for Medical Applications - Yow, K. S.; Javed, M. A.; Baig, A. Q.; Ahmad, M.; Ghareeb, S.; Qayyum, A. (Universiti Putra Malaysia, 2026)
Non-Kekule benzenoid structures are molecular systems that cannot be represented by classical Kekule resonance forms with alternating single and double bonds. These compounds often possess unpaired electrons and exhibit distinct electronic characteristics, including diradical and polyradical behavior. In this study, we analyze the structural and topological properties of selected non-Kekule benzenoid systems by computing various molecular descriptors, including the Atom-Bond Connectivity (ABC) index, Geometric-Arithmetic (GA) index, Randić index, First and Second Zagreb indices, Hyper Zagreb index and the Forgotten index. These topological indices offer valuable insights into the connectivity and branching patterns of the molecules, contributing to a deeper understanding of their structural complexity. The results may serve as a foundation for future investigations into the potential applications of these systems in fields such as materials science and molecular design.